2017
DOI: 10.1186/s12906-017-1569-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory potential of Capparis spinosa L. in vivo in mice through inhibition of cell infiltration and cytokine gene expression

Abstract: Background: Several chronic inflammatory diseases are characterized by inappropriate CD4+ T cell response. In the present study, we assessed the ability of Capparis spinosa L. (CS) preparation to orientate, in vivo, the immune response mediated by CD4+ T cells towards an anti-inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…flavonoids and tannins (Akkari et al, 2016). The anti-inflammatory activity of caper was also detected in animal studies, where leaf extracts were able to reduce edema in treated mice in a dose-dependent manner, as also a significant decrease in immune cells infiltration, vasodilatation and in dermis thickness (Azhary et al, 2017). Furthermore, leaf extracts of the same study inhibited the cytokine gene expression, namely IFNγ, IL-17 and IL-4 (Turgut et al, 2015).…”
Section: Health Effectsmentioning
confidence: 62%
“…flavonoids and tannins (Akkari et al, 2016). The anti-inflammatory activity of caper was also detected in animal studies, where leaf extracts were able to reduce edema in treated mice in a dose-dependent manner, as also a significant decrease in immune cells infiltration, vasodilatation and in dermis thickness (Azhary et al, 2017). Furthermore, leaf extracts of the same study inhibited the cytokine gene expression, namely IFNγ, IL-17 and IL-4 (Turgut et al, 2015).…”
Section: Health Effectsmentioning
confidence: 62%
“…Flavonoids reduce calcium accumulation in cells, which leads to a decrease in the activity of the nitric oxide synthase and phospholipase A2. It has been reported that caper hydroalcoholic extract prevents the expression of inflammatory cytokines such as TNFα, IL1β, IL6, LTB4, superoxide anion, and IL4 (20).…”
Section: Discussionmentioning
confidence: 99%
“…This effect of caper is due to having high levels of quercetin. Caper also has an antioxidant effect and can produce an antinociceptive effect by inhibiting nitric oxide (11,20).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory response of human peripheral blood mononuclear cells (PBMCs) induced by C. spinosa leaf extracts results from the control of cytokine gene expression (El Azhary et al, 2017 ). Cytokines constitute a category of small proteins (~5–20 kDa) that are important in cell signaling and inflammatory response.…”
Section: Phytochemical Composition and Activitiesmentioning
confidence: 99%